Size effects in the conduction electron spin resonance of anthracite and higher anthraxolite. (2nd December 2015) - Tadyszak, Krzysztof; Strzelczyk, Roman; Coy, Emerson; Maćkowiak, Mariusz; Augustyniak‐Jabłokow, Maria A.
Abstract : Electron paramagnetic resonance spectroscopy of conduction electrons, i.e. Conduction Electron Spin Resonance (CESR), is a powerful tool for studies of carbon samples. Conductive samples cause additional effects in CESR spectra that influence the shape and intensity of the signals. In cases where conduction electrons play a dominant role, whilst the influence of localized paramagnetic centres is small or negligible, the effects because of the spins on conduction electrons will dominate the spectra. It has been shown that for some ratios of the bulk sample sizes ( d ) to the skin depth ( δ ), which depend on the electrical conductivity, additional size effects become visible in the line asymmetry parameter A /| B |, which is the ratio of the maximum to the absolute, minimum value of the resonance signal. To study these effects the electrical direct current–conductivity and CESR measurements are carried out for two amorphous bulk coal samples of anthracite and a higher anthraxolite. The observed effects are described and discussed in terms of the Dyson theory. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The electron paramagnetic resonance (EPR) spectroscopy of materials with high electrical conductivity is influenced by conduction electrons. For the fixed temperature, the asymmetry of the Dysonian EPR signal depends on the ratio d/δ between sample size and skin depth. Interplay between these two factors and the crystal lattice properties, which determine the spin relaxation time, is responsible for the appearance of the signal asymmetry parameter anomalies observed for some values of d/δ ratio.